The evolution of the Si iv content in the Universe from the epoch of reionization to cosmic noon. Issue 2 (28th February 2022) - D'Odorico, V; Finlator, K; Cristiani, S; Cupani, G; Perrotta, S; Calura, F; Cènturion, M; Becker, G; Berg, T A M; Lopez, S; Ellison, S; Pomante, E
ABSTRACT: We investigate the abundance and distribution of metals in the high-redshift intergalactic medium and circum-galactic medium through the analysis of a sample of almost 600 Si iv absorption lines detected in high- and intermediate-resolution spectra of 147 quasars. The evolution of the number density of Si iv lines, the column density distribution function, and the cosmic mass density are studied in the redshift interval 1.7 ≲ z ≲ 6.2 and for log  N (Si iv ) ≥ 12.5. All quantities show a rapid increase between z ∼ 6 and z ≲ 5 and then an almost constant behaviour to z ∼ 2 in very good agreement with what is already observed for C iv absorption lines. The present results are challenging for numerical simulations: When simulations reproduce our Si iv results, they tend to underpredict the properties of C iv, and when the properties of C iv are reproduced, the number of strong Si iv lines [log  N (Si iv ) > 14] is overpredicted.